A D-Band Dual-Polarized High-Gain LTCC-Based Reflectarray Antenna Using SIW Magnetoelectric-Dipole Elements - Zhuo-Wei Miao (Micromachines)
This paper presents a D-band dual linear-polarized wideband high-gain reflectarray (RA) antenna using low-temperature co-fired-ceramic (LTCC) technology. The proposed element comprises a dual-polarized magnetoelectric (ME) dipole and a multilayer slot-coupling substrate-integrated waveguide (SIW) phase-delay structure, which are organized in accordance with the receiving/reradiating (R/R) principle. The coverage of phase shifts for both orthogonal polarizations is set to be greater than 360 degrees by varying the length of the phase-delay structure. For verification, a D-band 1296-element RA prototype using the proposed unit cell is fabricated and measured in a THz chamber. The measured results show that the proposed RA achieves a peak gain of 32.25 and 33.03 dBi for the two orthogonal polarizations. The measured 3 dB gain bandwidths for the two orthogonal polarizations are 122–149 GHz (20%) and 123–149 GHz (19.3%), respectively.